+0  
 
+5
267
2
avatar

prove 

sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)
I tried to make it with no sucsess
Many thanks

Guest Feb 24, 2017

Best Answer 

 #2
avatar+18369 
+25

prove 
sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)

 

\(\begin{array}{|rcll|} \hline && \frac{\sec^2(x)\cdot \csc^2(x)}{\csc^2(x) - \sec^2(x)} \\ &=& \frac{1}{ \frac{\csc^2(x) - \sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{\csc^2(x)}{\sec^2(x)\cdot \csc^2(x)} -\frac{\sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{1}{\sec^2(x)} -\frac{1}{ \csc^2(x)} } \quad & | \quad \frac{1}{\sec(x)}=\cos(x) \quad \frac{1}{ \csc(x)}=\sin(x) \\ &=& \frac{1}{ \cos^2(x) - \sin^2(x) } \quad & | \quad \cos(2x) = \cos^2(x) - \sin^2(x) \\ &=& \frac{1}{ \cos(2x) } \quad & | \quad \frac{1}{\cos(x)}=\sec(x)\\ &=& \sec(2x) \\ \hline \end{array} \)

 

laugh

heureka  Feb 24, 2017
Sort: 

2+0 Answers

 #1
avatar+75324 
0

sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)    simplify the right side

 

(sec^2x*csc^2x)/ (csc^2x - sec^2x)   =

 

( 1/cos^2x * 1 / sin^2x)  / ( 1/sin^2x -  1/cos^2x)  =

 

Get a common denominator for the fractions in the denominator  = sin^2xcos^2x

 

[ 1/(cos^2x sin^2x)] / [ ( cos^2x - sin^2x) / ( sin^2x cos^2x) ]  =

 

Invert the fraction in the denominator and multiply by the numerator

 

[ 1/(cos^2x sin^2x) ] * (sin^2x cos^2x)  / [cos^2x - sin^2x]  =

 

1 / [ cos^2x  - sin^2x ] =

 

1/ cos2x    =

 

sec2x

 

 

 

cool cool cool

CPhill  Feb 24, 2017
 #2
avatar+18369 
+25
Best Answer

prove 
sec2x = (sec^2x*csc^2x)/ (csc^2x - sec^2x)

 

\(\begin{array}{|rcll|} \hline && \frac{\sec^2(x)\cdot \csc^2(x)}{\csc^2(x) - \sec^2(x)} \\ &=& \frac{1}{ \frac{\csc^2(x) - \sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{\csc^2(x)}{\sec^2(x)\cdot \csc^2(x)} -\frac{\sec^2(x)}{\sec^2(x)\cdot \csc^2(x)} } \\ &=& \frac{1}{ \frac{1}{\sec^2(x)} -\frac{1}{ \csc^2(x)} } \quad & | \quad \frac{1}{\sec(x)}=\cos(x) \quad \frac{1}{ \csc(x)}=\sin(x) \\ &=& \frac{1}{ \cos^2(x) - \sin^2(x) } \quad & | \quad \cos(2x) = \cos^2(x) - \sin^2(x) \\ &=& \frac{1}{ \cos(2x) } \quad & | \quad \frac{1}{\cos(x)}=\sec(x)\\ &=& \sec(2x) \\ \hline \end{array} \)

 

laugh

heureka  Feb 24, 2017

8 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details